Strengthening the Role and Function of the Child Social Welfare Institution (LKSA) of Orphanages: Literature Analysis and Best Practices in Child Care and Education - Rosita; Alfitri; M. Mustaqim (Universitas Muhammadiyah Palu, 2024)
This research aims to strengthen the role and function of the Children's Social Welfare Institution (LKSA) of the Orphanage in the care and education of children, especially orphans from underprivileged, abandoned and exposed to promiscuity. Relevant journal articles are compiled using Harzing's Publish or Perish and the selected articles are publications from 2022-2024. From the journal articles that have been collected, it is found that: (1) The institution provides caregiving, educational, business-related services and guidance for foster children, (2) Chairmen, administrators and caregivers act as motivators, advisors, facility providers and to achieve a prosperous future in a safe and supportive environment, children are helped to prepare themselves to face various challenges in their lives, (3) Facing obstacles such as the limited number of caregivers, financial constraints, and lack of experience of caregivers in caring for and fostering children who have diverse characters and backgrounds, (4) The proposed strategy includes strengthening cooperation between caregivers, foster children, and families/guardians, the implementation of targeted joint activities, (5) Support for entrepreneurship skills training, marketing practices for processed food products and sewing skills (6), mental health education and character education efforts through the internalization of religious and socio-religious moderation values. The implementation of this concrete step is in line with the Regulation of the Minister of Social Affairs of the Republic of Indonesia No. 15 of 2010 and No. 30 of 2011, with the aim of creating a safe and fair environment for children, as the next generation who need comprehensive protection.